The mitochondrial genome and ribosomal operon of Brachycladium goliath (Digenea: Brachycladiidae) recovered from a stranded minke whale - Briscoe, Andrew G; Bray, Rodney A; Brabec, Jan; Littlewood, D T J (Parasitology international, 2016)
Members of the Brachycladiidae are known to cause pathologies implicated in cetacean strandings and it is important to develop accurate diagnostic markers to differentiate these and other helminths found in cetaceans. Brachycladium goliath (van Beneden, 1858) is a large trematode found, as adults, usually in the hepatic (bile) and pancreatic ducts of various cetaceans. Complete sequences were determined for the entire mitochondrial genome, and phylogenetically informative nuclear genes contained within the ribosomal operon, from a small piece of an individual worm taken from a common minke whale Balaenoptera acutorostrata Lacépède, 1804. Genomic DNA was sequenced using an Illumina MiSeq platform. The mtDNA is 15,229 bp in length consisting of 12 protein-coding genes, 22 tRNA genes, 2 rRNA genes and 2 non-coding regions of which the larger is comprised of 4 tandemly repeated units (260 bp each). The ribosomal RNA operon is 9297 bp long. These data provide a rich resource of molecular markers for diagnostics, phylogenetics and population genetics in order to better understand the role, and associated pathology of helminth infections in cetaceans.
Keywords: operon; tandemové repetitivní sekvence; Animals; Trematoda; Hologenophore; plejtvák malý; Female; Digenea; DNA, Mitochondrial; Genome, Mitochondrial; ženské pohlaví; nemoci ryb; NGS; Operon; Fish Diseases; genom mitochondriální; Tandem Repeat Sequences; Cetacea; Minke Whale; Phylogeny; Genetics, Population; Balaenoptera acutorostrata; mitochondriální DNA; Sequence Analysis, DNA; zvířata; sekvenční analýza DNA; fylogeneze; populační genetika